Biodistribution of newly synthesized PHEA-based polymer-coated SPION in Sprague Dawley rats as magnetic resonance contrast agent [Corrigendum] - Park J (Dove Medical Press, 2014)
Park J, Cho W, Park HJ, et al. Int J Nanomed. 2013;8(1):4077–4089. On page 4077, please note that Sun-Hang Cho’s affiliation was given as "5Korea United Pharm Inc, Seoul, Republic of Korea". The correct affiliation for Sun-Hang Cho is "3Biomaterials Laboratory, Korea Research Institutes of Chemical Technology, Daejeon, Republic of Korea".Read the original article